Identificação e análise molecular de isolados de Leptospira spp. de bovinos em Minas Gerais - Maria Raquel Venturim Cosate (2012)
Leptospirosis is caused by pathogenic spirochetes of the genus Leptospira spp. This zoonotic disease is distributed globally and affects domestic animals, including cattle. In livestock production, Leptospira interrogans serogroup Sejroe serovar Hardjo and Leptospira borgpetersenii serogroup Sejroe serovar Hardjo remain important species associated with this reproductive disease. Previous studies on Brazilian livestock have reported that L. interrogans serovar Hardjo is the most prevalent leptospire agent in this country and that it is related to leptospirosis clinical signs, leading to economic loss in production. Here, we focused on describing the isolation of three clinical strains obtained from leptospirosis outbreaks. Serological and molecular typing using housekeeping genes (secY and 16SrRNA), rfb locus genes (ORF 14, ORF15, ORF22, ORF36), virulent gene (LigB) and mobile elements (IS1500 and IS1533) were applied for the identification and comparative analysis of Leptospira spp. Our results confirmed the isolation of L.interrogans serovar Hardjo in Brazilian livestock. Genetic analysis using ORF22 and ORF36 lead us to group leptospira into serogroup taxonomic degree of classification. Genetic approaches were also applied to compare leptospira strains using IS1500 and IS1533 copy number analysis. The results suggest genetic variability among L. interrogans serovars species of reference bacterial strains and clinical isolates, which may contribute to leptospirosis identification and bacterial genetic variability. Furthermore, the results allow us to identify our three isolates (Norma, Lagoa and Bolivia) as belonging to L. interrogans species. Finally, we performed the whole genome sequence of Norma strain and distinct virulence associated genes profile were detected. Those results may contribute to improving the identification and epidemiological studies of leptospirosis in livestock production.